Genomics of Peripheral T-Cell Lymphoma and Its Implications for Personalized Medicine - Zhang, Yumeng; Lee, Dasom; Brimer, Thomas; Hussaini, Mohammad; Sokol, Lubomir (Frontiers in Oncology, 2020)
Peripheral T-cell lymphoma (PTCL) is a rare, heterogenous group of mature T-cell neoplasms that comprise 10% to 15% of non-Hodgkin lymphoma cases in the United States. All subtypes of PTCL, except for ALK+ anaplastic T-cell lymphoma, are associated with poor prognosis, with median overall survival (OS) rates of 1 to 3 years. The diagnosis of PTCL is mainly based on clinical presentation, morphologic features, and immunophenotypes. Recent advances in genome sequencing and gene expression profiling have given new insights into the pathogenesis and molecular biology of PTCL. An enhanced understanding of its genomic landscape holds the promise of refining the diagnosis, prognosis, and management of PTCL. In this review, we examine recently discovered genetic abnormalities identified by molecular profiling in 3 of the most common types of PTCL: RHOAG17V and epigenetic regulator mutations in angioimmunoblastic T-cell lymphoma, ALK expression and JAK/STAT3 pathway mutations in anaplastic T-cell lymphoma, and T-follicular helper phenotype and GATA3/TBX21 expression in PTCL-not otherwise specified. We also discuss the implications of these abnormalities for clinical practice, new/potential targeted therapies, and the role of personalized medicine in the management of PTCL.